A Mobley Theory to Predict Organizational Commitment as a Media Factor on Turnover Intention: A Structure Equation Model - Sarantie, Ade; Indrawati, Ratna; Mulyani , Erry Yudhya (Alta Dharma Publisher, 2022)
Background: In hospitals, competent human resources are needed in their fields. one of which is a nurse who has the responsibility and authority in providing nursing services to patients for 24 hours. Objective: The study aimed to examine the effect of work motivation, and compensation on turnover intention of inpatient nurses at Hospital X with organizational commitment as a mediating variable. Method: This study applied the quantitative with survey approach. Result: The results showed that the work motivation variable had a negative effect on turnover intention, this was indicated by the estimate value = -0.348 P-Values = 0.001 < = 0.05. Compensation has a negative effect on turnover intention, this is indicated by the value estimate = -0.288 P-Values = 0.004 < = 0.05. Organizational commitment has a negative effect on turnover intention, this is indicated by the value estimate = -0.350 P-Values = 0.014 < = 0.05. Work motivation has a positive effect on organizational commitment, this is indicated by the value estimate = 0.435 P-Values = 0.000 < = 0.05. Compensation has a positive effect on organizational commitment, it is indicated by the value estimate = 0.304 P-Values = 0.000 < = 0.05. Conclusion: Work Motivation and Compensation Variables have an effect on Turnover Intention mediated by Organizational Commitment